2020
DOI: 10.1177/2158244020962824
|View full text |Cite
|
Sign up to set email alerts
|

Primary Care for Transgender Individuals: A Review of the Literature Reflecting a Canadian Perspective

Abstract: Literature related to transgender health in adults has focused on definitions, hormone therapy, and transgender-sensitive care provision. Further understanding is needed on the delivery of primary care for transgender adults. The aim of this review was to understand the primary-care needs and access to health care services for transgender adults in Canada. A state-of-the-art literature review was conducted. Thirteen research studies were included. There is limited literature on the delivery of primary care for… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
13
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 40 publications
0
13
0
3
Order By: Relevance
“…Tese barriers still exist for TGNC people who are linked with a primary care provider as many TGNC people are uncomfortable talking to their doctor about trans-specifc health issues [5]. Coverage for trans healthcare in Canada varies widely by province [6], with some jurisdictions absorbing the costs of hormone replacement therapy and gender-afrming surgeries.…”
Section: Introductionmentioning
confidence: 99%
“…Tese barriers still exist for TGNC people who are linked with a primary care provider as many TGNC people are uncomfortable talking to their doctor about trans-specifc health issues [5]. Coverage for trans healthcare in Canada varies widely by province [6], with some jurisdictions absorbing the costs of hormone replacement therapy and gender-afrming surgeries.…”
Section: Introductionmentioning
confidence: 99%
“…1 Some of the primary care needs of transgender and cisgender people are similar, such as the need for preventive care, periodic health screening and examinations, and acute care visits. 2,3 Furthermore, rates of chronic disease, such as diabetes, cancer, osteoporosis, and cardiovascular disease, are similar within the transgender and cisgender population. 4 However, accessing cross-gender hormone therapy is a unique difference.…”
Section: Introductionmentioning
confidence: 99%
“…A recent review of the Canadian landscape identified the lack of practitioner knowledge as a key barrier to TGD persons accessing primary care [ 17 ]. Obedin-Maliver et al.…”
Section: Introductionmentioning
confidence: 99%
“…A recent review of the Canadian landscape identified the lack of practitioner knowledge as a key barrier to TGD persons accessing primary care [17]. Obedin-Maliver et al [5] found that more than a third of North American schools had no core LGBTQ+ content in their curricula, and even those that did tended to focus more on LGB and intersex topics than on those specific to TGD patients.…”
Section: Introductionmentioning
confidence: 99%